Medicolegal X-Ray and CT of standard size mobile phone cards (SIM card). - Schweitzer, Wolf; Winklhofer, Sebastian; Thali, Michael J.; Yaakup, Nur Adura; Abdul Rashid, Saiful Nizam (Elsevier, 2013)
Background. Foreign body ingestion typically affects children or adults with mental conditions. SIM (subscriber identity module) card ingestion is extremely rare. As their particularly X-Ray dense metal parts are sized about 9 × 12 mm × 50--80 μ, they can be difficult to capture on plain radiographs. We were asked by investigative authorities to point out the best method to document intentionally swallowed SIM cards.